Odontogenic myxoma, case report and literature review - Jerez Robalino, James (2020)
The odontogenic myxoma is a benign lesion that occurs mostly between the second and fourth decade of life, more frequently in the molar area and with a higher incidence in men than in women (2:1). Histologically, it presents starred and fusiform cells dispersed in a very abundant myxoid matrix. The objective of this article is to report a clinical case of an odontogenic myxoma, as well as a brief review of the literature. Subject: a 39-year-old female patient who attended the Oral and Maxillofacial Surgery clinic due to an increase in volume located in the jaw in the vestibular area between teeth 31 and 44; asymptomatic at palpation, with an evolution of approximately twelve months. An incisional biopsy was performed for the histopathological study. The result of the histopathological study was an odontogenic myxoma, so we decided that the best treatment was a free margin resection and reconstruction plate placement.